Extraction of Biochemical Compounds in Dates using Three Mixture Design and Identification by GC-MS and LC-TOF-MS with Principal Components Analysis - Taffaha A. Arhouma
In this study, the extraction using different solvents (chloroform, methanol and hexane) with reagent N,O-bis(trimethylsilyl) trifluoroacetamide (BSTFA) and 1% trimethyl- chlorosilane’ (TMCS) and their mixtures were used to extract biochemical compounds in three types of dates Kheseab (Tamar), Segae (Rutab) and Khalas (Tamar). The compounds were determined using Gas chromatography-mass spectrometry (GS-MS) and Liquid chromatography time-of-flight mass spectrometer (LC-TOF-MS). The results of GC-MS showed that the extraction using the mixture of methanol and chloroform (50% : 50%) extracted 16 compounds followed by methanol with hexane (50% : 50%) which extracted 15 compounds, and mixture of three solvents (33.3% : 33.3% : 33.3%)b14 compounds. While the other mixture of solvents, less number of compounds were extracted as compared with the previous mixtures. The results of LC- TOF-MS showed that the extraction using methanol and chloroform (50% : 50%) in Khalas (Tamar) was able to extract 27 compounds followed by Segae (Rutab) with 17 compounds while in Kheseab (Tamar) only 10 compounds were extracted. Principal Components Analysis (PCA) was performed on multivariate data of GS-MS results to study the relationship between compounds extracted with polarity of solvents mixture from the scores and loadings plots.